Clinical outcomes following surgical management of brain abscess in a tertiary care centre: retrospective analysis of 56 cases - Chandra, V. V. Ramesh; Prasad, B. C. M.; Niranjan, V.; Barde, Nitin Manohar (International Journal of Research in Medical Sciences, 2020)
Background: Despite the advent of newer antibiotics and surgical strategies, the overall outcome and quality of life issues in Brain Abscess (BA) patients remain a continuous challenge for the neurosurgical community. Methods: Fifty-six patients with BA are analyzed retrospectively, that treated between January 2014 and June 2019, according to age, the clinical symptoms, etiologic factors, infecting organisms, prognostic factors, localization, diagnostic and treatment methods and outcome. Results: In acute cases, common clinical features were headache, fever, vomiting, focal deficit and seizure. In chronic abscesses, common clinical features were mild to moderate headache and progressive focal deficit. In 12(21.42%) patients had adjacent localized sinus, middle ear infection. In 27(48.21%) patients no primary source of infection was identified, predisposing factors included post neurosurgery (8.92%), post penetrating injury (3.57%), and congenital heart disease, infective endocarditis, sinusitis. The frontal lobe involved in 28.5% cases, temporal lobe and cerebellum are next to be involved. Burr hole aspiration in 29(51.78%) cases, a craniotomy was done in 15(26.78%) cases. Pus culture was negative in 36 (64.28%) cases. Mortality was noted in 2(3.57%) cases. Complete resolution of the abscess with complete recovery of preoperative neuro-deficit was seen in 71.42% cases and recovery with major neuro-deficit was observed in 16.07% cases. The best outcome was seen with a better Glasgow Coma Scale (GCS) on admission. Conclusions: BA, when surgery is required, should be done on an emergency basis. BA treated with burr hole aspiration shows excellent clinical and radiological response. A craniotomy is required in selected cases and is a primary procedure in cerebellar, postoperative and posttraumatic abscesses. Broad-spectrum antibiotic therapy should be administered for a period of minimum 6 weeks to prevent relapse.